Pengaruh Komunikasi dan Pengetahuan terhadap Kinerja Pegawai pada Dinas Perumahan dan Kawasan Permukiman Kabupaten Banyumas - Potoru, Andreas Yoesbil Alison; Siska, Elmira; Indra, Natal (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to determine how much influence communication and work knowledge have on employee performance at the Department of Housing and Settlement Areas, Banyumas Regency. The research method used is a quantitative approach with sampling techniques using saturated jampel which is part of non-probability sampling with a total of 46 respondents. Collecting data using a questionnaire with a Likert scale. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression test, t test, and F test. The results of this study show that partially, communication has a positive influence on performance. Partially, knowledge has a positive and insignificant effect on performance. Simultaneously, communication and knowledge have no significant effect on performance